Manufacturing Value Added Development in North Africa: Analysis of Key Drivers - Anyanwu, John C. (Asian Development Policy Review, 2017)
It is widely recognized that structural transformation lies at the heart of economic development of any nation. Recent research suggests that the industrial sector, especially manufacturing, is a key engine of growth in the development process, including that of North Africa. The necessity for structural transformation in North Africa arises from the fact that the sub-region needs high and sustained economic growth in order to make significant progress in generating increased productive and quality jobs and livelihood for its teeming population, especially the youth. Unfortunately, manufacturing development in North Africa has not improved over time. For example, its manufacturing value added (MVA) in world MVA accounted for only 0.10 percent of world MVA in 2013. Also, the share of North African MVA in GDP was just 16.00% in 2013 compared with Asia & Pacific’s 25%. This paper empirically assesses the key drivers of manufacturing value added in the sub-region using a time series cross-sectional data set of the countries for the period, 1990 to 2014. Two estimation techniques, the pooled panel OLS regression with year fixed effects and the IV-2SLS estimation procedure, were used. There is also a strong support for a non-monotonic, cubic (third degree polynomial) relationship between MVA with economic development. The following factors are found to exert significant positive effect on manufacturing added in North Africa: secondary education, agricultural land, domestic credit to the private sector, trade openness, inward stock of FDI, population size, and ICT infrastructure/technology. On the other hand, the results indicate that dependence on oil, mineral and natural gas rents, domestic investment rate, political globalization, institutionalized democracy, age dependency ratio (young), and civil violence have significant negative effect on MVA in the sub-region. The paper concludes with policy recommendations.